Exploring the RNA-Recognition Mechanism Using Supervised Molecular Dynamics (SuMD) Simulations: Toward a Rational Design for Ribonucleic-Targeting Molecules? - Bissaro, Maicol; Sturlese, Mattia; Moro, Stefano (Frontiers in Chemistry, 2020)
If so far proteins have represented the molecular target of choice in the development of new drug candidates, the pharmaceutical importance of ribonucleic acids has been gradually growing. The increasing availability of structural information has brought to light the existence of peculiar RNAs three-dimensional arrangements, which can, contrary to initial expectations, be recognized and selectively modulated by means of small chemical entities or peptides. The application of classical computational methodologies, such as molecular docking, for the rational development of RNA binding candidates is however complicated by the peculiarities characterizing these macromolecules, first of all the marked conformational flexibility, the singular charges distribution and the relevant role of solvent molecules. In this work we have thus validated and extended the applicability domain of SuMD, an all-atoms molecular dynamics protocol that allows to accelerate the sampling of molecular recognition events in a scale of nanoseconds timescale, to ribonucleotides targets of pharmaceutical interest. In particular, the methodology ability in reproducing with an impressive degree of accuracy the binding mode of viral or prokaryotic ribonucleic complexes, as well as that of artificially engineered aptamers, has been proved.